Micro Mineral Profile Of Cattle In Four Selected Areas Of Mymensingh District - Shahjalal, M; Khaleduzzaman, ABM; Khandaker, ZH (Bangladesh Journal of Animal Science, 2012)
The experiment was undertaken with a view to investigate the micro mineral profile of feed and cattle at four agro-ecological zones (Haluaghat, Nandail, Trishal and Karimgonj upazila) in Mymensingh district. The differences (P>0.05) of copper (Cu), zinc (Zn), iron (Fe) and manganese (Mn) in rice straw, road side grass and fallow land grasses for different land type were not found. The average mineral concentration (ppm) of straw was 6.12, 24.93, 291.3, and 224.9 for Cu, Zn, Fe and Mn respectively. The values for Fe and Mn contents were higher and Cu and Zn contents were lower than the critical value. Both the road side and fallow land grasses contained adequate amount of Cu, Zn, Fe and Mn. The Cu and Zn content of blood serum did not vary significantly (P>0.05) among the cattle of four different land types. Based on 0.65 ppm serum Cu as critical level indicated a higher percentage of samples were below the critical level. Besides, increased incidence of Zn deficiency in medium high land (42%) and very low land (35%) was observed. All samples analyzed 66% were deficient in Cu content and 23% cattle were deficient in Zn. Land type differences (P<0.05) were found for blood serum Fe and Mn. The average Fe concentration in very low land gave significantly (P<0.05) higher value than that of high, medium high and low land. Serum Fe and Mn concentrations of all samples were above the critical level of 1.0 ppm and 20 μg/ml respectively and the animals were not deficient in Fe and Mn. The liver Cu concentration was similar (P>0.05) in four different regions. The overall incidence of liver samples deficient in Cu was 53% for all land types. No significant (P>0.05) difference in liver Zn concentration was recorded among the samples collected from different land types and none of cattle liver samples was deficient in Zn as well as Fe and Mn concentration. From the results of the present study, it is evident that low concentration of Cu and Zn in rice straw reflected in the blood samples of the animals suggesting the need of extra supplementation of these two elements to the cattle feed of Mymensingh district. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9867 BJAS 2008; 37(1): 44-52